Six-year incidence and progression of diabetic retinopathy in Indian adults: the Singapore Indian Eye study. Issue 12 (2nd February 2019) - Kumari, Neelam; Bhargava, Mayuri; Nguyen, Duc Quang; Gan, Alfred Tau Liang; Tan, Gavin; Cheung, Ning; Tan, Nicholas; Wong, Charlene; Wang, Jie Jin; Mitchell, Paul; Lamoureux, Ecosse L; Cheng, Ching Yu; et al.
Abstract : Aims: Diabetes is a major public health problem in migrants and ethnic minorities worldwide. We determined the incidence and risk factors of diabetic retinopathy (DR) in migrant Indians living in Singapore. Methods: We included data from 759 Indian adults with diabetes, who participated in the baseline (aged 40–80 years, 2007–2009) and 6-year follow-up 2012–2015 of the Singapore Indian Eye Study. Retinal photographs were graded for the presence and severity of DR using modified Airlie House Classification. Incidence was assessed in participants who were free of DR at baseline visit (n=501), while progression in those with DR but free of proliferative DR at baseline visit (n=189). Risk factors included demographic, lifestyle, socioeconomic, family history, genes, duration of diabetes, glycaemic control, insulin use, ocular and clinical factors. Results: The 6-year age-standardised DR incidence and progression were 21.89% and 33.45%, respectively. HbA1c (risk ratio (RR) 1.41, 95% CI 1.28 to 1.55 per unit increase), current smoking (RR 1.63, 95% CI 1.02 to 2.62) and insulin use (RR 2.63, 95% CI 1.44 to 4.82) were associated with higher incidence, whereas estimated cerebrospinal fluid pressure (RR 0.90, 95% CI 0.82 to 0.98) and body mass index (BMI) (RR 0.74, 95% CI 0.60 to 0.93) were associated with lower incidence of DR. Higher HbA1c (RR 1.26, 95% CI 1.13 to 1.42), BMI (RR 1.26, 95% CI 1.02 to 1.56) and estimated cerebrospinal fluid pressure (RR 1.11, 95% CI 1.02 to 1.21) were associated with DR progression. The population attributable risk of HbA1c >8% was 41.29% and 49.63% for DR incidence and progression. Conclusion: DR incidence and progression in migrant Indians living in Singapore was more than double that reported in Indians living in urban India. Consistent with past studies, poor glycaemic control was an important predictor for incidence and progression of DR.